Titanium laminate, and method for producing titanium laminate

JP2025021086AActive Publication Date: 2025-02-13TOHO TITANIUM CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023124807
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-02-13
Estimated Expiration
2043-07-31

AI Technical Summary

Benefits of technology

【0020】 この発明のチタン積層体によれば、電解質膜への損傷を抑制することが可能であり、さらに、優れた通気性ないし通液性を実現することができる。この発明のチタン積層体の製造方法は、そのようなチタン積層体の製造に適したものである。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025021086000001
    Figure 2025021086000001
Patent Text Reader

Abstract

To provide a titanium laminate and a method for producing the titanium laminate that are able to inhibit damage to an electrolyte membrane while achieving excellent air or liquid permeability.SOLUTION: A titanium laminate according to this invention has a sheet-like shape, and is provided with a plurality of gas-liquid-permeable layers, which are made of titanium and laminated such that titanium bonding surfaces adjacent in the lamination direction are bonded to one another, and which each have holes through which a gas and / or a liquid can pass. At least a gas-liquid-permeable layer of the plurality of gas-liquid-permeable layers which forms one of the laminate surfaces is a porous layer having a thickness of 500 μm or less. In the one laminate surface, the average value of the area of the holes that open to the laminate surface is from 4 μm2 to 17 μm2 inclusive, the standard deviation value of the area of the holes is 20 μm2 or less, and the number of holes in a rectangular region having an aspect ratio of 4:3 and an area of 22000 μm2 is 120 or more. In the other laminate surface positioned on the rear side relative to the one laminate surface, the average value of the area of the holes that open to the laminate surface is at least three times the average value of the area of the holes in the one laminate surface.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sheet-like titanium laminate having a porous layer and a method for manufacturing the titanium laminate. [Background technology]

[0002] Porous titanium bodies produced by sintering titanium powder or titanium fibers have air or liquid permeability due to their pores, and electrical conductivity. They also have high corrosion resistance due to the formation of a passive film on the surface.

[0003] Porous titanium with such properties is being considered for use in porous transport layers (PTLs) in polymer electrolyte membrane (PEM)-type water electrolysis equipment, which are in environments where corrosion may occur. In particular, hydrogen produced in PEM-type water electrolysis equipment using electricity derived from renewable energy is called "green hydrogen," and is attracting great expectations in recent years as the movement toward a decarbonized society accelerates.

[0004] Patent Document 1 discloses a metal fiber nonwoven sintered sheet having a total thickness of less than 1 mm, including a main layer and at least one auxiliary layer laminated on the main layer and integrally sintered therewith, the main layer being made of metal fibers having a thickness of 1 to 10 μm and having a porosity of 80% or more, the auxiliary layer being made of metal fibers having a thickness at least twice that of the metal fibers of the main layer, the total thickness of the auxiliary layer being less than 2.5 times that of the main layer, and the total porosity of the main layer and auxiliary layer being 75% or more and 90% or less. Patent Document 1 also describes that the main layer and auxiliary layer are preferably made of corrosion-resistant metal materials such as stainless steel, titanium alloys, nickel alloys, and copper alloys, and can be suitably used not only for filtering fuel oils, lubricating oils, water, dyes, inks, etc., which have been conventionally used, but also for filtering high-temperature liquids, organic solvents, acids, alkalis, etc.

[0005] Patent Document 2 describes "a fuel cell power supply unit that is constructed by integrating a porous titanium plate having through holes with a titanium matrix portion having voids," and "a method for producing a fuel cell power supply unit that includes the steps of providing a large number of through holes in a titanium raw plate, stacking the plate and a titanium raw member that will become the matrix portion, applying pressure to the stacked plate and raw member of the matrix portion, and heating the plate and raw member of the matrix portion to which the pressure has been applied." With regard to the "method for producing a fuel cell power supply unit," it is described that "the step of stacking the plate and raw member of the matrix portion includes a step of arranging a binder together with the raw member of the matrix portion, and further includes a step of removing the binder," and that "the binder is a mixture of a water-soluble alkoxide and boron nitride, and the step of removing the binder includes a removal step using alcohol."

[0006] Patent Document 3 states that in "a method for producing a sheet-like porous sintered body, which is characterized by producing a titanium fiber molding having a minor axis of 10 to 100 μm and a major axis of 1 to 10 mm, and then placing a plate material on the molding and sintering it while pressing," it states that "sintered body 61 of titanium fibers 3 is preferably placed on sintered substrate 5 which is less likely to melt-bond to titanium fibers or titanium alloy fibers even when it comes into contact with them." [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2000-129311 A [Patent Document 2] JP 2004-185946 A [Patent Document 3] JP 2007-70727 A Summary of the Invention [Problem to be solved by the invention]

[0008] When a titanium porous body is used as a porous transport layer in a PEM-type water electrolysis device, the titanium porous body may be pressed against the electrolyte membrane when assembled. If the pores on the surface of the titanium porous body are large, the electrolyte membrane pressed against the titanium porous body may partially enter the pores and may be significantly deformed in the vicinity of the pores, which may cause damage to the electrolyte membrane. Furthermore, if there are protrusions on the surface of the titanium porous body, the electrolyte membrane may be damaged. Such protrusions are often present on the surface of the titanium porous body, which is a sintered body of a fibrous material. Titanium porous bodies manufactured using fibrous materials tend to have large pores on the surface as described above.

[0009] Therefore, from the viewpoint of preventing damage to the electrolyte membrane, it is desirable for the titanium porous body to have small pores that open to the surface facing the electrolyte membrane. Even if the pores are small, a certain degree of air or liquid permeability can be achieved as long as there are a large number of pores.

[0010] However, when the pores in a titanium porous body are small throughout, high air permeability or liquid permeability cannot be obtained even if the number of pores is large. For this reason, it is difficult to significantly improve air permeability or liquid permeability while suppressing damage to the electrolyte membrane with a single titanium porous body.

[0011] An object of the present invention is to provide a titanium laminate that is capable of suppressing damage to an electrolyte membrane and achieving excellent air and liquid permeability, and a method for manufacturing a titanium laminate. [Means for solving the problem]

[0012] The inventors have intensively studied to solve the above-mentioned problems, and have come up with a sheet-like titanium laminate in which a plurality of gas-liquid permeable layers are laminated. Here, one surface side of the laminate is a gas-liquid permeable layer of a porous layer having relatively small pores opening on the laminate surface so that damage to the electrolyte membrane is suppressed when the laminate is pressed against the electrolyte membrane in a PEM-type water electrolysis device. However, in order to ensure the required air permeability or liquid permeability even on the one surface side of the laminate, the gas-liquid permeable layer has a relatively large number of pores on the one surface side of the laminate formed thereby. In addition, in order to increase the air permeability or liquid permeability of the titanium laminate as a whole, the thickness of the porous layer having small pores on the one surface side of the laminate is made thin. On the other hand, a gas-liquid permeable layer having relatively large pores opening on the surface side of the laminate is positioned on the other surface side of the one surface of the laminate.

[0013] The titanium laminate of the present invention is in the form of a sheet, and is laminated by bonding adjacent titanium bonding surfaces to each other in the lamination direction, and comprises a plurality of titanium gas-liquid permeable layers each having pores through which gas and / or liquid can pass, and at least one of the gas-liquid permeable layers forming one of the laminate surfaces is a porous layer having a thickness of 500 μm or less, and the average area of ​​the pores opening to the laminate surface on the one of the laminate surfaces is 4 μm. 2 More than 17μm 2 The standard deviation of the area of ​​the hole is 20 μm or less. 2 and the area is 22000μm 2 the number of holes present within a rectangular region having an aspect ratio of 4:3 is 120 or more, and the average area of ​​the holes opening onto one of the laminate surfaces, on the other laminate surface located on the reverse side of the one of the laminate surfaces, is three times or more the average area of ​​the holes on the one of the laminate surfaces.

[0014] In the titanium laminate, it is preferable that the gas / liquid permeable layer forming one of the laminate surfaces has the smallest thickness among the plurality of gas / liquid permeable layers.

[0015] In the titanium laminate, each of the plurality of gas / liquid permeable layers is preferably a porous layer.

[0016] The method for producing a titanium laminate of the present invention is a method for producing a sheet-like titanium laminate, which includes a bonding step of using a plurality of titanium gas-liquid permeable materials each having pores through which gas and / or liquid can pass, wherein at least one of the gas-liquid permeable materials forming the surface of the laminate is a porous material having a thickness of 500 μm or less, and bonding the titanium bonding surfaces of the plurality of gas-liquid permeable materials together while contacting each other with their respective titanium bonding surfaces and sandwiching and pressing the gas-liquid permeable material between pressing surfaces of opposing pressing members, while heating the gas-liquid permeable material to a temperature of 810°C or more and 1100°C or less, and bonding the titanium bonding surfaces of the plurality of gas-liquid permeable materials together, wherein the bonding step uses a pressing member whose pressing surface is coated with boron nitride particles using a coating agent that does not contain water.

[0017] In the above manufacturing method, the coating on the pressing surface may be a coating agent in which boron nitride particles are dispersed in an organic solvent.

[0018] In the above manufacturing method, it is preferable that the joining step uses, as the pressing member, a pressing member made of graphite having the coating applied to the pressing surface.

[0019] In the above manufacturing method, the average area of ​​the pores opening on the surface of the porous material of the gas-liquid permeable material forming at least one of the laminate surfaces before bonding in the bonding step is 5 μm 2 More than 17μm 2 The standard deviation of the area of ​​the hole is 20 μm or less. 2 and the area is 22000μm 2 It is preferable that the number of the holes present in a rectangular region having an aspect ratio of 4:3 is 250 or more. Effect of the Invention

[0020] The titanium laminate of the present invention can suppress damage to the electrolyte membrane and can achieve excellent air and liquid permeability. The method for producing such a titanium laminate of the present invention is suitable for producing such a titanium laminate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Hereinafter, an embodiment of the present invention will be described in detail. The titanium laminate according to one embodiment of the present invention comprises a plurality of titanium gas-liquid permeable layers each having a pore and allowing gas and / or liquid to pass therethrough, and these gas-liquid permeable layers are laminated by bonding adjacent titanium bonding surfaces in the lamination direction. At least one of the gas-liquid permeable layers forming the surface of the laminate on one side is a porous layer having a thickness of 500 μm or less.

[0022] The titanium laminate has a surface formed of a gas-liquid permeable layer as a porous layer, and the average area of ​​the pores opening on the surface of the laminate is 4 μm 2 More than 17μm 2 The standard deviation of the hole area is 20 μm 2 and the area is 22000μm 2 The number of holes present within a rectangular region having an aspect ratio of 4:3 is 120 or more. When the average value and standard deviation of the area of ​​the holes opening on one of the laminate surfaces are small in this way, the holes opening on one of the laminate surfaces have a relatively small and uniform area, so that when the titanium laminate is pressed against an electrolyte membrane in a PEM-type water electrolysis device on one of the laminate surfaces, damage to the electrolyte membrane can be suppressed. In addition, since there are a relatively large number of holes opening on one of the laminate surfaces, the required air permeability or liquid permeability can be ensured on the one of the laminate surfaces.

[0023] In contrast, a predetermined gas / liquid permeable layer is positioned on the other laminate surface located behind one of the laminate surfaces of the titanium laminate so that the average area of ​​the holes opening on that laminate surface is at least three times the average area of ​​the holes on one of the laminate surfaces. This allows gas or liquid to easily permeate through the gas / liquid permeable layer on the other laminate surface side, greatly improving the air permeability or liquid permeability of the titanium laminate as a whole.

[0024] In order to manufacture the above titanium laminate, it is necessary to bond and laminate a plurality of titanium gas-liquid permeable materials corresponding to the plurality of gas-liquid permeable layers. However, if the plurality of titanium gas-liquid permeable materials are simply sandwiched between the opposing pressing surfaces of a pressing member and pressed while being heated to a predetermined temperature, the titanium porous gas-liquid permeable material will bond to the pressing member, making it difficult to peel it off from the pressing member. Therefore, in the bonding step of this embodiment, a pressing member having a pressing surface coated with boron nitride particles is used. The coating of boron nitride particles suppresses the reaction between the material of the pressing member and the titanium gas-liquid permeable material. In addition, when a pressing member made of boron nitride is used, the boron nitride peels off and adheres to the titanium laminate, and when it is peeled off, the surface of the laminate tends to become rough. However, in this embodiment, the pressing member has a pressing surface coated with boron nitride particles, so such a problem is unlikely to occur. This makes it possible to manufacture the above titanium laminate.

[0025] (Titanium laminate) The titanium laminate is made of titanium. If it is made of titanium, it can be said that the titanium laminate has high electrical conductivity at a certain relative density. The titanium content of the titanium laminate (and further each gas-liquid permeable layer) is preferably 97% by mass or more, and more preferably 98% by mass or more. The upper limit of the titanium content is not limited to this, but may be, for example, 99.8% by mass or less, or 99% by mass or less. This titanium content means the purity of titanium taking into consideration not only metal components but also impurities of gas components such as oxygen. Therefore, the titanium content can be calculated by subtracting the total content of metal components and impurity components including gas components from 100% by mass.

[0026] The titanium laminate (particularly the gas / liquid permeable layer of the porous layer on one surface side of the laminate) may contain Fe as an impurity, and may also contain Ni, Cr, Al, Cu, Zn, and Sn as unavoidable impurities resulting from the manufacturing process. The Fe content may be, for example, 0.25 mass% or less. It is preferable that each of the contents of Ni, Cr, Al, Cu, Zn, and Sn is less than 0.10 mass%, and that the total content of these elements is less than 0.30 mass%.

[0027] The oxygen content of the titanium laminate is not particularly limited, but may be 0.4% by mass or more and 2.0% by mass or less. The oxygen content of the titanium laminate may be 1.0% by mass or more and 2.0% by mass or less. The oxygen content can be measured by inert gas fusion-infrared absorption method.

[0028] The titanium laminate may have a purity equivalent to pure titanium type 1 to 4, typically type 1 to 2, of JIS H 4600 (2012), excluding the carbon, nitrogen, and oxygen contents.

[0029] The titanium laminate is in the form of a sheet and includes a plurality of titanium gas-liquid permeable layers. The plurality of gas-liquid permeable layers are laminated by bonding adjacent titanium bonding surfaces in the lamination direction. When the titanium laminate is manufactured by the manufacturing method described below, the titanium bonding surfaces of the titanium gas-liquid permeable material are bonded to each other, so that the titanium bonding surfaces are bonded to each other in the titanium laminate. It is preferable that the interface of the plurality of gas-liquid permeable layers is substantially free of metals other than titanium or compounds not containing titanium, in that a required high electrical conductivity can be achieved at low cost. This is because the cost increases when a layer containing another metal such as platinum is provided to bond the gas-liquid permeable layers to each other in order to suppress an increase in electrical resistance at the interface. Each of the plurality of gas-liquid permeable layers has a hole portion and is permeable to gas and / or liquid. The titanium laminate as the porous transport layer of the PEM water electrolysis device may be permeable to gas and / or liquid in other directions, such as the lamination direction (sheet thickness direction) or a direction perpendicular to the lamination direction.

[0030] One of the laminate surfaces of the titanium laminate is formed by a gas / liquid permeable layer (also referred to as "gas / liquid permeable layer on one side") constituting the portion on the surface side of that one of the laminates, and this laminate surface corresponds to the surface of the gas / liquid permeable layer on one side. The gas / liquid permeable layer on one side is a porous layer. The porous layer is formed by bonding titanium powder particles together, and has a sponge-like three-dimensional mesh structure in which pores are formed between the bonded titanium powder particles. By making the gas / liquid permeable layer on one side a porous layer with the above-mentioned three-dimensional mesh structure, the one of the laminate surfaces is more likely to have a large number of minute openings of a predetermined number, as described below.

[0031] The average area of ​​the holes on one surface of the laminate is 4 μm 2 More than 17μm 2 If the pores on one of the laminate surfaces have a relatively small area, the laminate surface can be said to be generally smooth, and damage to the electrolyte membrane in the PEM water electrolysis device can be effectively suppressed. From this viewpoint, the average area of ​​the pores on one of the laminate surfaces is set to 4 μm2 More than 10μm 2 It is preferable that the standard deviation of the hole area on one of the laminate surfaces is 20 μm or less. If the average area of ​​the holes on one of the laminate surfaces is too small, the air permeability or liquid permeability may decrease. If the average area of ​​the holes on one of the laminate surfaces is too large, the electrolyte membrane may partially enter the holes and be significantly deformed in the vicinity of the holes, which may cause damage to the electrolyte membrane. From the same viewpoint, it is preferable that the standard deviation of the hole area on the laminate surface is 20 μm or less. 2 Below that, another 3 μm 2 ~20μm 2 , especially 5 μm 2 ~17μm 2 A small standard deviation value means that most of the pores present on one of the laminate surfaces are as small as required.

[0032] In addition, on one of the laminate surfaces, the area is 22000 μm 2 The number of holes present in a rectangular region having an aspect ratio of length:width = 4:3 is 120 or more, preferably 140 or more, and more preferably 150 or more. The presence of many fine holes as described above on one of the laminate surfaces ensures the required air permeability or liquid permeability while realizing smoothness. The number of holes in the rectangular region on one of the laminate surfaces is not limited to this, but may be, for example, 400 or less, or 300 or less.

[0033] The other laminate surface of the titanium laminate means the surface located on the back side or opposite side of one laminate surface, and is formed by the gas-liquid permeable layer constituting the portion on the other laminate surface side (also referred to as the "gas-liquid permeable layer on the other side"). In other words, the other laminate surface corresponds to the surface of the gas-liquid permeable layer on the other side.

[0034] In order to improve the air permeability or liquid permeability of the titanium laminate, the average value of the area of ​​the holes opening on the other laminate surface is preferably 3 times or more, more preferably 5 times or more, or even 7 times or more, of the average value of the area of ​​the holes on one laminate surface. In this way, by forming the other laminate surface side with a gas-liquid permeable layer having large holes, gas and liquid can easily flow inside the titanium laminate. The upper limit of the average value of the area of ​​the holes opening on the other laminate surface is not particularly limited, provided that it has a required strength for use when incorporated in, for example, a PEM water electrolysis device. As an example, it is 200,000 times or less, 10,000 times or less, 1000 times or less, 500 times or less, or 100 times or less of the average value of the area of ​​the holes on one laminate surface. Since the expanded metal, mesh, punched metal, etc. described later may have large holes that are visible to the naked eye, the upper limit of the average value of the area of ​​the holes opening on the other laminate surface may be as large as 200,000 times or less.

[0035] The gas-liquid permeable layer on the other side is not limited to a porous layer having a three-dimensional mesh structure, and may be, for example, an expanded metal layer, mesh layer, or punched metal layer in which holes of a certain size are regularly formed penetrating in the thickness direction, as long as the average value of the area of ​​the holes on the surface of the other laminate is a predetermined value. From the viewpoint of controlling the flow of gas or liquid to some extent by gradually increasing the size of the holes in the titanium laminate, it is preferable that the gas-liquid permeable layer on the other side is also a porous layer. However, even in this case, in order to ensure that the average value of the area of ​​the holes opening on the surface of the other laminate is three times or more the average value of the area of ​​the holes on the surface of one of the laminates, in the manufacture of the titanium laminate, porous materials having different properties or obtained by different manufacturing methods can be used as the gas-liquid permeable materials for the gas-liquid permeable layers on one side and the other side. Note that the porous layer as the gas-liquid permeable layer on the other side can be not only one formed by bonding titanium powders to each other, but also one having a nonwoven three-dimensional mesh structure or mesh structure formed by bonding titanium fibers to each other. A porous material having a three-dimensional network structure produced by sintering a fiber raw material has a nonwoven fabric-like shape and has protrusions on its surface, but has the characteristic of having a certain degree of strength and large pores. Therefore, when a sintered body of a fiber raw material is used as a gas-liquid permeable material in a position not in contact with the electrolyte membrane, it is easy to ensure excellent air or liquid permeability while obtaining the desired strength.

[0036] The average value and standard deviation of the area of ​​the holes opening on the laminate surface and the number of holes in a predetermined rectangular region are measured using a scanning electron microscope (Keyence Ultra-Deep Multi-Angle Lens VHX-D510). More specifically, for one side of the laminate surface, the average value and standard deviation of the area of ​​the holes opening on the laminate surface are measured using a scanning electron microscope (Keyence Ultra-Deep Multi-Angle Lens VHX-D510). 2A SEM image is obtained at a magnification of 2000 times for a rectangular region with an aspect ratio of 4:3. For the surface of the laminate on the other side, the aspect ratio is the same as above, 4:3, and the observation magnification and the surface area are set according to the size of the holes on the surface of the laminate on the other side. Specifically, the magnification and the surface area are set so that the number of holes, which is the observation result of the surface of the laminate on the other side, is within the range of 100 to 1000. In particular, when the other side is a porous layer, a small grain removal process and a hole filling process are performed in the identification of the holes, as described later, so that by taking an image within the range of the number of holes, the average value of the hole area of ​​the laminate surface on one side and the laminate surface on the other side can be compared more accurately. When the other side is a porous layer, the observation magnification may be preferably 900 times. Then, the SEM image is analyzed using a scanning electron microscope, and a value of half the maximum detection value of the brightness of the SEM image is set as a threshold value, and a closed region with a brightness in the range of 0 to the threshold value is regarded as one hole. At this time, the SEM image may be subjected to a binarization process as necessary. After the binarization process, a small grain removal process (processing to black pixels after binarization) is performed for closed regions of 50 pixels or less, and then a hole filling process (processing to white pixels after binarization) is performed for closed regions of 50 pixels or less. Using this, the number and area of ​​each hole are calculated, and the standard deviation value is obtained as the square root of the variance. Such an analysis of the SEM image is performed for five rectangular regions on the laminate surface, at least some of which are offset from each other, and the average value of the area and the average value of the number of holes in these rectangular regions are respectively the average value and standard deviation of the area of ​​the holes on the laminate surface and the number in the rectangular region. In the case of a laminate surface that is a square or rectangular rectangle in a plan view, the above five rectangular regions are the five rectangular regions at the center and the four corners.

[0037] The thickness of the sheet-like titanium laminate (total thickness including all gas-liquid permeable layers) may be 40 μm or more and 1000 μm or less. For example, a porous transport layer of a PEM water electrolysis device may require such a relatively thick titanium laminate. On the other hand, if the thickness is too large, the PEM water electrolysis device may become large. The thickness of the titanium laminate may be, for example, 700 μm or less, 400 μm or less, or 350 μm or less, or may be 40 μm or more, or 80 μm or more.

[0038] The thickness of the titanium laminate is measured at a total of five points, four points on the periphery and one point in the center of the titanium porous body, using a digital thickness gauge with a flat gauge having a Φ10 mm measuring probe and a measurement accuracy of 0.01 mm, such as a Mitutoyo digital thickness gauge (model number 547-321), and the average of these measured values ​​is used. When the sheet-like titanium porous body is rectangular in plan view, the four peripheral points are the four corner points.

[0039] The thickness of the gas / liquid permeable layer on one side is 500 μm or less, and preferably 40 μm to 400 μm, 40 μm to 300 μm, or 40 μm to 200 μm. Since the gas / liquid permeable layer on one side is a porous layer with small pores, if the thickness is too thick, the air permeability or liquid permeability of the titanium laminate as a whole decreases. On the other hand, by making the thickness of the gas / liquid permeable layer on one side thicker to some extent, the required strength is ensured after sintering during the preparation of the corresponding porous material, and the gas / liquid permeable layer is less likely to crack when pressed against the electrolyte membrane together with other gas / liquid permeable layers. The gas / liquid permeable layer on one side is preferably the thinnest among the multiple gas / liquid permeable layers. By making the thickness of the gas / liquid permeable layer on one side, which has small pores and is difficult for gas or liquid to permeate, the air permeability or liquid permeability of the titanium laminate can be greatly improved.

[0040] The thickness of the gas-liquid permeable layer on the other side is preferably 100 μm to 960 μm. By making the thickness of the gas-liquid permeable layer on the other side thicker to a certain extent, the air permeability or liquid permeability can be further improved, and by not making it too thick, the water electrolysis device can be made smaller and the electrolysis efficiency per area can be improved.

[0041] The thickness of each gas / liquid permeable layer is measured by observing the thickness at five points on the cross section in the thickness direction of the titanium laminate that has been embedded in resin and polished using an SEM, and the average value is used. Since the functions required of each gas / liquid permeable layer in the titanium laminate are different, a portion where the difference in pore size in the stacking direction is identified, and the thickness of each gas / liquid permeable layer is obtained by SEM observation of that portion.

[0042] The surface area of ​​the sheet-like titanium laminate in plan view is not particularly limited and can be appropriately determined depending on various conditions. For example, it is 70 mm 2 More than 600,000 mm 2 Below, 10000mm 2 ~600000mm 2 The above-mentioned "sheet-like" refers to a plate-like or foil-like shape having a small thickness compared to the dimensions in a plan view, and there is no particular restriction on the shape in a plan view.

[0043] The titanium laminate can be constructed of two gas-liquid-permeable layers, with one gas-liquid-permeable layer and the other gas-liquid-permeable layer directly bonded at their titanium bonding surfaces, but it is also possible to provide one or more intermediate gas-liquid-permeable layers between the one gas-liquid-permeable layer and the other gas-liquid-permeable layer. One or more of the intermediate gas-liquid-permeable layers can be porous layers, or they may be expanded metal layers, mesh layers, punched metal layers, or the like. When each of the multiple gas-liquid-permeable layers is a porous layer, the pores in the titanium laminate can be gradually enlarged to control the flow of gas or liquid to a certain extent.

[0044] (Manufacturing method) To manufacture the above-mentioned titanium laminate, first, a plurality of gas-liquid permeable materials corresponding to the plurality of gas-liquid permeable layers of the titanium laminate are prepared. At least one of the gas-liquid permeable materials forming one of the laminate surfaces of the titanium laminate (the gas-liquid permeable material for the gas-liquid permeable layer on one side) is a porous material having a thickness of 500 μm or less. At least one of the other gas-liquid permeable materials may be an expanded metal material, a mesh material, a punched metal material, or the like, but is preferably a porous material.

[0045] The expanded metal material, mesh material, or punched metal material that can also be used as the gas-liquid permeable material can be purchased. The porous material may be a commercially available product, or it can be prepared as described below.

[0046] An example of a method for making a porous material includes the steps of paste making, drying, debinding and sintering in that order, and may be referred to as the paste method.

[0047] In the paste preparation step, a crushed powder such as titanium hydride / dehydrogenated powder or titanium hydride powder, or a spherical powder such as atomized powder, or other titanium powder, an organic binder, and an organic solvent are mixed using a mixer with an agitator, a rotary mixer, a triple roll mill, or the like to prepare a paste. At this time, the mixture may be crushed using a vibration mill, a bead mill, or other crushing mixer, or the like.

[0048] The average particle size of the titanium powder contained in the paste can be, for example, 25 μm or less, preferably 18 μm or less. By using titanium powder with such a small particle size and further using a specific dispersant as described below, a porous material with a smooth surface can be obtained. The average particle size of the titanium powder can be 5 μm or more, and even 10 μm or more. The average particle size means the particle size at which the cumulative distribution on a volume basis is 50% in the particle size distribution obtained by the laser diffraction scattering method.

[0049] As the organic binder used in the paste, various types can be appropriately selected and used, and examples thereof include methyl cellulose, polyvinyl alcohol, ethyl cellulose, acrylic, polyvinyl butyral, etc. An organic binder exhibiting hydrophobicity is preferable. However, it is not limited to the ones listed here. The organic solvent is, for example, alcohol (ethanol, isopropanol, terpineol, butyl carbitol, etc.). As an example, the organic binder may be polyvinyl butyral and the organic solvent may be isopropyl alcohol. The paste may further contain a plasticizer (glycerin, ethylene glycol, etc.) and a surfactant (alkylbenzene sulfonate, etc.).

[0050] When manufacturing a porous material to be used as one of the gas / liquid permeable layers, the paste does not contain water as a solvent. It is preferable that the paste also does not contain a foaming agent. The paste may contain water as a solvent, and water that may be unintentionally mixed into the paste due to moisture absorption or the like is permitted. If a porous material is manufactured using a paste containing water and / or a foaming agent, large pores are formed during the manufacturing process, making it impossible to achieve the desired pore size.

[0051] Regardless of the case of manufacturing a porous material for one of the gas / liquid permeable layers, the paste is applied relatively thinly onto a substrate and dried, for example, at a temperature of 90°C to 165°C for 5 minutes to 300 minutes in a drying process. This is followed by a binder removal process, in which the substrate is heated, for example, at a temperature of 300°C to 450°C for 3 hours to 12 hours to volatilize and remove the organic binder.

[0052] Then, a sintering process is performed, and the sintering temperature is set to, for example, 1.0×10 -2 The titanium powder is sintered by heating at a temperature of 700°C to 1000°C for 1 hour to 4 hours in a vacuum of 1 Pa or less or in an inert atmosphere of Ar or He. This produces a porous material.

[0053] Another example of a method for producing a porous material, although a detailed description will be omitted, is a method (dry method) in which titanium powder or titanium fibers are dropped and deposited in a gas such as air or in a vacuum, and then this is heated in a reduced pressure atmosphere such as a vacuum to sinter it.

[0054] When the porous material for one of the gas-liquid permeable layers is manufactured by the above-mentioned paste method, the average area of ​​the pores opening on the surface of the obtained porous material is 5 μm 2 More than 17μm 2 The standard deviation of the hole area is 20 μm 2 and the area is 22000μm 2 The number of the pores present within a rectangular region having an aspect ratio of 4:3 may be 250 or more. The standard deviation of the area of ​​the pores opening to the surface of the porous material may be further 3 μm 2 ~20μm 2 , especially 10 μm 2 ~20μm 2 When such a porous material is used as the gas / liquid permeable material forming one of the laminate surfaces and a bonding step, which will be described later, is carried out, the shape of the pores changes, and in the gas / liquid permeable layer on one side of the titanium laminate, the average area and number of pores opening to one of the laminate surfaces may become the values ​​described above.

[0055] After the multiple sheets of gas-liquid permeable material are prepared, a bonding step is performed in which the sheets are bonded and laminated. More specifically, in the bonding step, the titanium bonding surfaces of the multiple sheets of gas-liquid permeable material are brought into contact with each other. If necessary, the multiple sheets of gas-liquid permeable material may be partially fixed to each other by welding or the like. However, since fixing by welding or the like may partially narrow or eliminate the pores of the gas-liquid permeable material or reduce its thickness, it is preferable to simply overlap the multiple sheets of gas-liquid permeable material and bring them into contact without fixing them.

[0056] In this state, the gas / liquid permeable materials are sandwiched and pressed from both sides between the opposing flat pressing surfaces of the pressing members, while being heated to a temperature of 810°C or more and 1100°C or less, preferably 850°C or more and 1000°C or less. As a result, the multiple gas / liquid permeable materials are laminated by bonding their titanium bonding surfaces together through solid-phase diffusion, forming a titanium laminate. Note that the above temperature is the maximum temperature that can be reached by heating.

[0057] In the bonding process, it is essential to use a pressing member, such as a setter, whose pressing surface is coated with boron nitride particles. A pressing member made of graphite or the like that is not coated on the pressing surface reacts with titanium when heated in the bonding process, and impurities such as TiC may be formed on one of the laminate surfaces, which is particularly smooth and has a large contact area, of the titanium laminate. On the other hand, if a pressing member made of boron nitride is used, boron nitride having self-lubricating properties may peel off and adhere to the laminate surface, and the laminate surface may become rough when peeled off. In contrast, a pressing member whose pressing surface is coated with boron nitride particles can suppress the formation of impurities on the laminate surface, and even if boron nitride particles adhere to the laminate surface, they can be easily removed by washing with water, etc. In addition, when a pressing member whose pressing surface is coated with boron nitride particles is used, it is also easy to separate the titanium laminate from the pressing member after the bonding process.

[0058] In order to coat the pressing surface of the pressing member with boron nitride particles prior to the bonding step, a coating agent in which boron nitride particles are dispersed in an organic solvent can be used, for example, by spraying the coating agent onto the pressing surface and then drying the coating agent. The particle size of the boron nitride particles used for coating is preferably 9 μm or less, more preferably 5 μm or less, and even more preferably 3 μm or less. The particle size of the boron nitride particles means the diameter of a circle having the average area of ​​each particle calculated on a photographed image. From the viewpoint of suppressing the aggregation of the boron nitride particles attached to the pressing surface after coating, it is preferable to use an organic solvent, not water, as the coating agent. This suppresses the occurrence of uncoated portions on the pressing surface due to the generation of the aggregated particles, which causes the pressing surface to bond to the surface of the laminate, and the aggregated particles from penetrating into the interior of the laminate from the surface of the laminate, thereby affecting the breathability or liquid permeability.

[0059] Preferably, the pressing member is made of graphite and has a pressing surface coated with boron nitride particles as described above. The graphite pressing member is not easily peeled off even at high temperatures during the bonding process. In addition, the boron nitride particles are easily adsorbed to the pressing surface of the graphite pressing member.

[0060] The pressing and heating time in the bonding step may be, for example, 30 minutes to 8 hours at a temperature of 810° C. or higher. The bonding step may be performed in a reduced pressure atmosphere or an inert atmosphere. EXAMPLES

[0061] Next, a sheet-shaped titanium laminate according to the present invention was produced as a prototype, and the details thereof will be described below. However, the description here is merely for illustrative purposes and is not intended to be limiting.

[0062] As gas-liquid permeable materials having pores and allowing gas and / or liquid to pass through, three types of porous materials with different properties (WEBTi-K, WEBTi-T, and WEBTi-S ("WEBTi" is a registered trademark) manufactured by Toho Titanium Co., Ltd.) and an expanded metal material (Finemetal small mesh BD20 manufactured by Sanki Manufacturing Co., Ltd.) were prepared. All of these are made of titanium. WEBTi-K was produced by the paste method, WEBTi-T was produced by a dry method using titanium powder, and WEBTi-S was produced by a dry method using titanium fiber. WEBTi-K and WEBTi-T have a sponge-like three-dimensional mesh structure, and WEBTi-S has a nonwoven three-dimensional mesh structure.

[0063] Two types of gas-liquid permeable materials were selected from the above, and the titanium bonding surfaces were simply stacked together with contact between them. They were then sandwiched between pressing members from both sides, and heated while being pressurized to bond the titanium bonding surfaces together and laminated. The pressure was applied by placing a weight on the upper pressing member, and the pressure was 0.14 N / cm. 2 ~0.35N / cm 2 The gas-liquid permeable material was placed together with the pressing member in a furnace, and heating was performed at a temperature of 1000°C for 1 hour in Examples 1 to 4 and Comparative Examples 1 and 2, at a temperature of 1200°C for 1 hour in Comparative Example 3, and at a temperature of 775°C for 1 hour in Comparative Example 4.

[0064] Here, a graphite setter was used as the pressing member, and a coating of boron nitride particles was applied to the pressing surface by spraying a predetermined coating agent onto the pressing surface and then drying the coating. In Examples 1 to 4 and Comparative Examples 3 and 4, an organic solvent-based coating agent (Whitey Release-N manufactured by Odec Co., Ltd.) was used as the coating agent, which contains boron nitride particles in the range of 1% by mass to 5% by mass, an organic solvent containing 65% by mass or more of dimethyl ether, and does not contain water. In Comparative Example 1, BN Release (water-based coating agent) manufactured by Odec Co., Ltd. was used as the coating agent. This water-based coating agent has a water content in the range of 50 to 60% by mass and a dimethyl ether content in the range of 35 to 40% by mass. When the water-based coating agent was used, it was heated to about 100°C in order to dry after being sprayed onto the pressing surface. In Comparative Example 2, no coating was applied to the pressing surface. In addition, in all of Comparative Examples 1 to 4, WEBTi-K and WEBTi-T were adopted as the two types of gas-liquid permeable materials. In addition, in all of Examples 1 to 4 and Comparative Examples 1 to 4, WEBTi-K was used as the gas-liquid permeable material, which is a porous material forming one of the laminate surfaces.

[0065] As a result, in Examples 1 to 4, a titanium laminate could be produced. On the other hand, in Comparative Example 1, the pressing surface of the pressing member was coated with a water-based coating agent, and thus aggregated boron nitride particles entered the titanium laminate. In Comparative Example 2, the pressing surface was not coated, and therefore the pressing surface and the laminate surface were bonded together, and they could not be peeled off. In Comparative Example 3, the pressing surface was coated, but the temperature at the time of bonding was too high, and therefore the pressing surface and the laminate surface were bonded together, and they could not be peeled off well. In Comparative Example 4, the temperature at the time of bonding was too low, and therefore the bonding between the gas-liquid permeable materials was weak. For this reason, in Comparative Examples 1 to 4, a titanium laminate could not be produced.

[0066] In addition, for each titanium laminate, the thickness, electrical conductivity, oxygen content, average value and standard deviation of the area of ​​the holes on the laminate surface, and the number of holes in a rectangular region were measured. The results are shown in Table 1. The standard deviation of the area of ​​the holes will be described later. The method for measuring the thickness, average value of the area of ​​the holes, standard deviation of the area of ​​the holes, and the number of holes in a rectangular region was as described above. In Example 3, the holes in the gas-liquid permeable layer formed of the expanded metal material were too large compared with the holes in WEBTi-S and the like in Example 1, so that the average value of the area of ​​the holes could not be measured. For this reason, in Table 1, the number of holes in the expand in Example 3 is set to "0", but this does not represent the actual number.

[0067] The electrical conductivity was measured for each laminate surface by the four-probe method using a Mitsubishi Analytec low resistivity meter Loresta GP MCP-T610, with the laminate surface to be measured positioned on the upper side. The probe checker used was the MCP-TRPS RMH311 for the laminate surface side of expanded metal, WEBTi-T, or S, and the MCP-TP06P RMH112 for the laminate surface side of WEBTi-K. It is considered that the electrical conductivity will be high if the titanium bonding surfaces of the gas-liquid permeable layers are sufficiently bonded together. In addition, when the electrical conductivity is high, it is assumed that the mechanical strength is also excellent because each gas-liquid permeable layer is firmly bonded. The electrical conductivity was measured for both sides of the manufactured titanium laminate, and both sides had a conductivity of 3.2×10 3 The conductivity of the upper gas-liquid permeable material was measured with two sheets of gas-liquid permeable material overlapped before bonding, and the results are also shown in Table 1.

[0068] In Comparative Example 4, the bonding temperature was low, so that the titanium bonding surfaces of the gas-liquid permeable layers were not bonded sufficiently, and the electrical conductivity of the WEBTi-K side was 2.5 × 10 3 Since the hardness was low at only 1.0 S / cm, it was determined that the titanium laminate could not be manufactured.

[0069] [Table 1]

[0070] In addition, the standard deviation of the area of ​​the holes in one surface of the titanium laminate of Examples 1 to 4 was measured by the above-mentioned method. 2 , 10.1 μm in Example 2 2 , 13.3 μm in Example 3 2 , and 7.6 μm in Example 4. 2 The standard deviation of the area of ​​the pores on the surface of the porous material forming one of the laminate surfaces before bonding used in the production of each of the titanium laminates in Examples 1 to 4 was 15.3 μm in Example 1. 2 , 12.4 μm in Example 2 2 , and 11.9 μm in Example 3. 2 , and 14.8 μm in Example 4. 2 It was.

[0071] According to this invention, it is possible to suppress damage to the electrolyte membrane, and further, it has been suggested that excellent air and liquid permeability can be achieved.

Claims

1. A sheet-shaped titanium laminate, The laminate is provided with a plurality of titanium gas / liquid permeable layers which are laminated by bonding adjacent titanium bonding surfaces in a lamination direction, each of which has a hole and is permeable to gas and / or liquid, Among the plurality of gas / liquid permeable layers, at least one gas / liquid permeable layer forming a surface of the laminate is a porous layer having a thickness of 500 μm or less, On the surface of the one laminate, the average area of ​​the holes opening onto the laminate surface is 4 μm 2 More than 17 μm 2 The standard deviation of the area of ​​the hole is 20 μm or less. 2 or less, and the area is 22000 μm 2 the number of holes present within a rectangular region having an aspect ratio of 4:3 is 120 or more; A titanium laminate, wherein the average area of ​​holes opening onto one of the laminate surfaces, on the other laminate surface located on the reverse side of the one of the laminate surfaces, is three or more times the average area of ​​holes on the one of the laminate surfaces.

2. 2. The titanium laminate according to claim 1, wherein the gas / liquid permeable layer forming the one of the laminate surfaces has the smallest thickness among the plurality of gas / liquid permeable layers.

3. 3. The titanium laminate according to claim 1, wherein each of the plurality of gas / liquid permeable layers is a porous layer.

4. A method for producing a sheet-shaped titanium laminate, comprising the steps of: A gas-liquid permeable material is made of a plurality of titanium sheets each having a hole and allowing gas and / or liquid to pass therethrough, and at least one of the gas-liquid permeable materials forming a laminate surface is a porous material having a thickness of 500 μm or less, The method includes a bonding step of heating the gas-liquid permeable material to a temperature of 810° C. or more and 1100° C. or less while sandwiching and pressing the gas-liquid permeable material between pressing surfaces of opposing pressing members in a state where the titanium bonding surfaces of the gas-liquid permeable material sheets are in contact with each other, thereby bonding the plurality of gas-liquid permeable materials to each other at the titanium bonding surfaces; A method for manufacturing a titanium laminate, wherein in the bonding step, a pressing member having a pressing surface coated with boron nitride particles using a coating agent that does not contain water is used as the pressing member.

5. The method for producing a titanium laminate according to claim 4, wherein the coating on the pressing surface is made of a coating agent in which boron nitride particles are dispersed in an organic solvent.

6. 6. The method for producing a titanium laminate according to claim 4, wherein the pressing member used in the bonding step is a pressing member made of graphite and having a pressing surface coated with the coating.

7. Before the bonding in the bonding step, the average area of ​​the pores opening on the surface of the porous material of the gas-liquid permeable material forming at least one of the laminate surfaces is 5 μm 2 More than 17 μm 2 The standard deviation of the area of ​​the hole is 20 μm or less. 2 or less, and the area is 22000 μm 2 6. The method for producing a titanium laminate according to claim 4 or 5, wherein the number of said holes present within a rectangular region having an aspect ratio of 4:3 is 250 or more.

Citation Information

Patent Citations

  • Metallic fiber non-woven fabric sintered sheet

    JP2000129311A

  • Power feeding body for fuel cell, and its manufacturing method

    JP2004185946A

  • Method for producing sheet-shaped porous sintered compact

    JP2007070727A